Ruídos do mau gosto: cuspes, conflitos e perspectivas urbanas na seção de cartas da revista Chiclete com Banana (1985 - 1990) - Romani, Aline Pimentel (2018)
The objective of this research is to investigate, through the magazine Chiclete with Banana, the social processes that made up the political and cultural changes of the 1980s in Brazil. When presenting the magazine, I try to understand the space occupied by it in the publishing market, verifying the meanings of being an alternative or counter-hegemonic magazine, and the importance of the collective work of the cartoonists and authors. Considering the re-democratization of the country, after twenty years of dictatorship, I analyzed the conflicts and disputes that surrounded urban spaces and the magazine section of letters. The central source of this work is the letters sent by the readers, valuing the subjects as protagonists of the processes of transformation of the city and culture, especially the young people. In addition, since much of the space is devoted to the section of letters, I pondered on its relevance in the composition of the journal, in the choice of topics and in the newspaper's publicity. However, the themes transcend the magazine and tell a lot about conflicts in public spaces and attitudes adopted in the daily lives of urban groups, as well as punks, head bangers, bald men, metal workers, skaters, among others.